Changing the Action of Iron from Stoichiometric to Electrocatalytic in the Hydrogenation of Ketones in Aqueous Acidic Media. Issue 21 (18th September 2015) - Gottardo, Marina; Easton, Max; Fabos, Viktoria; Guo, Si‐Xuan; Zhang, Jie; Perosa, Alvise; Selva, Maurizio; Bond, Alan M.; Masters, Anthony. F.; Maschmeyer, Thomas
Abstract: Cyclohexanone, a model compound chosen to conveniently represent small oxygenates present in the aqueous phase of biomass hydrothermal upgrading streams, was hydrogenated in the presence of electrodeposited iron(0) using aqueous formic or sulfuric acid as a hydrogen donor. Under these conditions, zero‐valent iron is consumed stoichiometrically and serves as both a formic acid decomposition site and a hydrogen transfer agent. However, the resulting iron(II) can be used to continuously regenerate iron(0) when a potential is applied to the glassy carbon working electrode. Controlled potential electrolysis experiments show a 17 % conversion of cyclohexanone (over 1000 seconds) to cyclohexanol with >80 % efficiency of iron deposition from an iron(II) sulfate solution containing formic or sulfuric acid. In the absence of electrodeposited iron, formation of cyclohexanol could not be detected. Abstract : Reduce, reuse, recycle : Cyclohexanone, a model compound for oxygenates present in biomass hydrothermal upgrading streams, is hydrogenated in the presence of electrodeposited iron using formic or sulfuric acid as the hydrogen donor. Zero‐valent iron operates as an effective electrocatalyst (17 % conversion, 1000 s, >80 % efficiency) that can be continuously regenerated.